P93 The complex process of risk assessment in liver transplantation: what do second opinions tell us?. (16th November 2010) - Gera, A; O'Grady, J; Al-Freah, M; Heneghan, M; Aluvihare, V; Suddle, A; Auzinger, G; Prachalias, A; Srinivasan, P; Heaton, N; Wendon, J; Agarwal, K
Abstract : Introduction: Liver transplant (LT) assessment involves a targeted evaluation of risk and benefit for any individual patient. In the context of limited organ supply, some patients with co-morbidities or marginal indications are declined on initial assessment. It is considered good practice to offer such patients a second opinion. Aim: To assess the indications and outcomes in patients referred for a second opinion to our transplant programme. Method: All patients who had been fully assessed and not accepted for LT in other units were identified. A retrospective review of patient notes and interrogation of a prospectively maintained database from December 2000 to May 2008 was performed. Baseline characteristics, indications for LT and 2-year survival were analysed. Results: 24 patients were referred from other institutions after having been declined listing. Reasons for initial decline ranged from cardiovascular risk in 8/24 (33.3%), HCV recurrence 2/24 (8.3%), HIV co-infection 2/24 (8.3%), technical suitability 2/24 (8.3%), substance misuse issues 2/24 (8.3%), other co-morbidities 5/25 (20.8%) and HCC on previous imaging felt to be beyond Milan criteria in 3/24 (12.5%). All underwent full reassessment and multidisciplinary review. Median age was 59 years (IQR 52–68 years), median MELD and UKELD at time of assessment were 17 (12–19) and 55 (51–60) respectively. 15/24 (63%) were male. Overall 16/24 (67%) were ultimately accepted for transplantation. For those again declined for transplantation, the reasons were confirmatory to those outlined at the referring hospital. Of those listed for LT 9/16 (56%) received a graft, 6 received cadaveric whole grafts, 3 received right lobe grafts (1 from a live donor, 1 non heart beating, 1 cadaveric split). In those who received a transplant 1-year survival was 100%, 2-year survival 89%. Mortality on the waiting list was 31% (5/16) with 1 patient currently awaiting LT, 1 patient was subsequently transplanted back at their original transplant centre. Those who died on the waiting list had higher median age, MELD scores, UKELD scores and were more likely to be blood group O (4/5, 80%). However these were not statistically significant. The median length of stay post LT was higher in the group referred for a second opinion and then transplanted (29 days, IQR 21–55) as compared to our standard population (22 days, IQR 15–40). Conclusion: Patients meeting guidelines for LT should be listed according to need. Our series demonstrates that a second opinion for LT can be beneficial for selected individual patients. Outcomes in selected cases can be optimal, although these patients theoretically represent higher operative risk. Mortality was associated with waiting times and blood group. These data support the utility of the second opinion component of the transplant assessment process.